Blockchain for humanitarian aid - Kustak, Tom (2020)
Blockchain technology has proven to be an effective tool to increase performance in for-profit supply chains. Yet, we lack deep understanding of its impact on the humanitarian supply chain. This thesis aims at addressing this gap through a qualitative research. Evidence from expert interviews and secondary reports suggests that blockchain technology positively impacts the information and resource flow in humanitarian supply chains by either replacing traditional intermediaries or enhancing transparency. It further reveals that the impact on supply chain actors is very individual. Donors can particularly benefit from the increased transparency as this empowers them to track their donations. Humanitarian organizations can improve their internal efficiencies and enhance their collaboration with external stakeholders. For beneficiaries, blockchain technology offers a new infrastructure to access humanitarian services which are more dignified and empowering. The empirical findings of this thesis enhance our general understanding of blockchain technology in the humanitarian sector. Furthermore, this research provides concrete strategies for humanitarian organizations to leverage the full potential of blockchain technology. Thus, it is of particular relevance for humanitarians aiming to address current challenges in the humanitarian supply chain.